Contribution of Expenditure to Agriculture Growth in Nepal (Quest Journal of Management and Social Sciences, 2023)
Background: Among the different macroeconomic sectors, agriculture is critical to the expansion of Nepal's economy. Agriculture is the main strength for the development of trade and the service industry. Agriculture has become the backward linkage for trade and service. The contribution of expenditure is vital for the growth and agricultural development of Nepal.Objectives: The purpose of the study is to determine contribution of expenditure to the agricultural economic growth in Nepal.Methodology: The descriptive and causal research designs were used for the study. Annual time series from 1974/75-2020/21 was used as the data. The research used the Auto-Regressive Distributed Lag model (ARDL) approach of cointegrationa. Moreover, unit root test, bound test, residual diagnostics and normality test were used.Results: The empirical result indicates a short run good association between the agriculture labor force, gross fixed capital formation, capital expenditure and total food crops and long term collaboration between the agriculture labor force, gross fixed capital formation, total food crops and total cash crops. The disequilibrium is corrected in the one lag period with a speed of adjustment of 0.07 per cent.Conclusions: The study concludes that there is an association between government expenditure to agriculture growth of Nepal. So, government spending and agriculture expansion are associated in the long run.Implications: Government expenditure must increase to escalate the economic growth of agriculture, reflected via a source of economic growth in Nepal.Originality: The study is purely original and nowhere published yet. Likewise, no grants have been obtained during the period of investigation on this issue.